Las posibilidades educativas del paradigma hipertextual: modelos y resultados de investigación - López-Andrada, Concepción (Colombian Applied Linguistics Journal, 2020)
This paper explores models and research findings that have originated from the growing need for experimental analysis on hypertext and its educational potential. The research that have been reviewed in this work offer a common framework that, on the one hand, extends in an institutional context; and on the other hand, contains what digital is as a means of diffusing knowledge implying novel and underlying dynamics. The development of reading competence and learning through hypertexts is described as a relatively recent field, in which it is inescapable to seek utility and projection of results to promote student learning through efficient use of hypertext for didactics. This concept of didactics is relevant as it is understood as a complex way to categorize information and meanings.